2021
DOI: 10.7717/peerj.12464
|View full text |Cite
|
Sign up to set email alerts
|

A decrease in reports on road-killed animals based on citizen science during COVID-19 lockdown

Abstract: Background To avoid the uncontrolled spread of COVID-19 in early 2020, many countries have implemented strict lockdown measures for several weeks. In Austria, the lockdown in early spring has led to a significant drop in human outdoor activities, especially in road traffic. In Project Roadkill, a citizen science project which aims to collect data on road-killed animals, we observed a significant decrease in reported roadkills. Methods By asking the citizen scientists through a survey how their travelling rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Our results in Table 4 are parallel to the study Frietas et al [25] who revealed his results of mortalities in which most of them Mammals (60%) followed by Birds (31%) and Reptiles (9%).Our results of both transacts reveal the same picture that the mortality of Mammals at site 1 is highest (56%) followed by Birds (22%) and Reptiles(21%).In case of study site 2 the highest mortality was recorded in case of Mammals (51%) followed by Birds (29%) and Reptiles (19%) [26]. These anamoly of result may be due to natural distribution of fauna in both study zones.…”
Section: Discussionsupporting
confidence: 74%
“…Our results in Table 4 are parallel to the study Frietas et al [25] who revealed his results of mortalities in which most of them Mammals (60%) followed by Birds (31%) and Reptiles (9%).Our results of both transacts reveal the same picture that the mortality of Mammals at site 1 is highest (56%) followed by Birds (22%) and Reptiles(21%).In case of study site 2 the highest mortality was recorded in case of Mammals (51%) followed by Birds (29%) and Reptiles (19%) [26]. These anamoly of result may be due to natural distribution of fauna in both study zones.…”
Section: Discussionsupporting
confidence: 74%
“…The pandemic did indeed appear to impact participation in CBC in 2020, both in the United States and in Canada, as seen in other parts of the world for other citizen science programs (Rose et al 2020;Dorler and Heigl 2021;Kishimoto and Kobori 2021;Sanchez-Clavijo et al 2021;Stenhouse et al 2022). Significantly fewer counts were conducted in 2020 compared with the totals that would be expected based on trends of the previous 10 years.…”
Section: Discussionmentioning
confidence: 93%
“…Some programs saw increases in participation (Basile et al 2021;Crimmins et al 2021), while others saw decreases (Rose et al 2020;Kishimoto and Kobori 2021), but participation changes depended on how the program was structured (Crimmins et al 2021). These effects were seen globally (Rose et al 2020;Crimmins et al 2021;Dorler and Heigl 2021;Kishimoto and Kobori 2021;Sanchez-Clavijo et al 2021;Stenhouse et al 2022), but were most pronounced during the strictest lockdowns during the spring and early summer of 2020. Within the United States, restrictions varied by state (Drill et al 2022), particularly by December, when CBC was scheduled.…”
mentioning
confidence: 96%
“…The survey results suggest that a majority of the respondents have reported less roadkills during the lockdown, regardless if they changed their travelling routine or not. The survey results combined with the general decrease in road traffic, suggested that fewer animals were killed during the lockdown 16 . To predict amphibian migration events in spring, we compared the migration of common toads ( Bufo bufo ) and common frogs ( Rana temporaria ) with the phenology of five tree, one shrub, and one herb species.…”
Section: Background and Summarymentioning
confidence: 97%